RADIATION DOSE OPTIMIZATION OF BREAST CANCER WITH PROTON THERAPY METHOD USING PARTICLE AND HEAVY ION TRANSPORT CODE SYSTEM - Milah Fadhilah Kusuma Fasihu; Andang Widi Harto; Isman Mulyadi Triatmoko; Gede Sutrisna Wijaya; Yohannes Sardjono (JURNAL TEKNOLOGI REAKTOR NUKLIR TRI DASA MEGA, 2021)
Radiotherapy is one of the cancer treatments conducted by giving a high dose to the tumor target and minimizing the dose exposed in the healthy organs. One of the methods is proton therapy. Proton therapy is usually used in several breast cancer cases by minimizing the damage in the surrounding tissues due to having good precision. In this study, proton therapy in breast cancer will be simulated. This study aims to identify the optimal dose in breast cancer therapy using proton therapy and to identify the dose exposed in the healthy organs surrounding cancer. This study is PHITS program simulation-based to model the geometry and the components of breast cancer and the surrounding organs. The source of radiation used is proton which is the output of proton therapy with proton/sec firing intensity. The variation in beam modelling towards the dose profile of the tumor used is uniform and pencil beam. The proton energy used is 70 MeV up to 120 MeV. The result of this study shows that the dose from using pencil beam scanning technic of proton therapy for breast cancer is 50.3997 Gy (W) with the total amount of fraction is 25 and the result of dose below the threshold dose in the healthy organs is the skin gets 4.4.0553 Gy per fraction, the left breast gets 0,0011 Gy per fraction, the right breast gets 2.6469 Gy per fractions, the right lung gets 0.0125 Gy per fraction, the left lung gets 0.029 Gy per fraction, the rib gets 0.0179 Gy per fraction, and the heart gets 0.0077 Gy per fraction.